Capturing drinking and nightlife behaviours and their social and physical context with a smartphone application – investigation of users' experience and reactivity. (2nd January 2020) - Labhart, Florian; Tarsetti, Flavio; Bornet, Olivier; Santani, Darshan; Truong, Jasmine; Landolt, Sara; Gatica-Perez, Daniel; Kuntsche, Emmanuel
Abstract: Background : Many addictive behaviours are influenced by the context in which they occur, but methods for simultaneously capturing the characteristics of a behaviour and its context are scarce. This study describes a smartphone application developed to document young adults' nightlife and drinking behaviours and investigates its impact on participants' lives. Methods : 241 participants, aged 16–25 (46.5% women), were asked to document 10 Friday and Saturday nights over seven weekends. Using their own smartphones, they documented the beverages consumed and the social and physical context by means of questionnaires, photos, and video clips, while phone sensors (e.g., GPS, Bluetooth, accelerometer) were running in the background. Quantitative and additional qualitative data (40 in-depth interviews) were used to investigate response burden, assessment reactivity, and disruption of usual activities among three participant groups, arranged according to the number of reports submitted during the study. Results : 69% of participants documented 10 or more nights. Compared with the most frequent contributors, regular and irregular participants reported similar numbers of non-alcoholic drinks per night, but lower numbers of alcoholic drinks. Within each group, the number of drinks consumed did not change over the course of the study. Taking pictures and video clips was sometimes perceived as inappropriate and potentially disruptive to the ongoing social activities. Conclusion : The application required a high but sustainable degree of commitment and did not induce reactivity. The method might be adapted to study other context-dependent addictive behaviours. Measures to decrease response burden and disruption of usual activities are proposed.